THE EFFECT OF INFLUENCER CREDIBILITY AND DIGITAL ADVERTISING ON AQUA BRAND PURCHASE DECISIONS WITH SATISFACTION CUSTOMER AS A MODERATING VARIABLE (Case Study of Aqua Instagram Followers) - Dedy Dwi Arseto (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
This study aims to determine the Effect of Influencer Credibility and Digital Advertising on Aqua Brand Purchase Decisions With Customer Satisfaction As Moderating Variable (Case Study of Aqua Instagram Followers). The research method used is a quantitative method using SPSS version 25.00. The data collected from the results of distributing questionnaires to employees are 100 respondents. The analytical method used in this study is to use an instrument test, namely the validity and reliability test. The classical assumption test is normality test, multicolonearity test, heteroscedasticity test, multiple linear regression analysis, coefficient of determination analysis (R2), hypothesis testing namely T test, F test and interaction test. The results of SPSS in this study are the influencer credibility variable (X1) has no effect on the purchasing decision level variable (Y), the digital advertising variable (X2) has no effect on the purchasing decision variable (Y), the influencer credibility variable (X1) and digital advertising ( X2) has a simultaneous effect on purchasing decisions (Y) and the interaction test shows that the calculation results obtained show that customer satisfaction (Z) can moderate the influencer credibility relationship (X1) on purchasing decisions (Y), customer satisfaction (Z) cannot moderate the relationship. digital advertising (X2) on purchasing decisions (Y).